An overview of theories on child maltreatment and their applicability to Zimbabwean society - Gwirayi, Pesanayi (African Journals Online, 2021)
Child maltreatment has become an issue of immense concern across the globe. Literature is unequivocal about the deleterious effects and consequences of child maltreatment on the social development and other life domains of the survivors. This paper traces theories that were developed in order to increase humanity’s understanding of the aetiology and epidemiology of child maltreatment, providing a basis upon which this social vice could be fought. The discussion focuses on theories considered by many researchers to constitute important contributions in broadening human society’s understanding of the various contexts in which child maltreatment occurs. The theories discussed in the paper are categorized as follows: psychological, sociological, social learning and ecological approaches. They are considered in the context of their applicability to Zimbabwean society. The review of the theories suggests that, no one-dimensional theory will sufficiently explain the exceptions of its premise, thereby giving credence to the need to employ multidimensional approaches to the study of child maltreatment. Accordingly, the ecological–transactional framework was found to be the most comprehensive and rigorous explanatory model for child maltreatment.